Comprehensive Analysis of Physical, Mechanical, Wettability, Shear, and Bonding Performance Properties of Rubberwood Various Trunk Diameters and Radial Positions Bonded with Various Adhesives for Sustainable Engineered Timber Construction: Bibliometric and Experimental Insights toward the Sustainable Development Goals (SDGs) - Suthon Srivaro; Sataporn Jantawee (Bumi Publikasi Nusantara, 2026)
This study presents a comprehensive analysis of the physical, mechanical, wettability, shear, and bonding performance properties of rubberwood within and between trunks of various diameters bonded with different adhesives for sustainable engineered timber construction. Rubberwood samples from trunks of different sizes were tested for density, modulus of rupture, modulus of elasticity, compressive strength, shear strength, and wettability. Polyvinyl acetate (PVAc) and polyurethane (PUR) adhesives were applied under varying clamping pressures to evaluate bonding strength and wood failure behavior. The results revealed minimal variation in physical and mechanical properties across radial positions and trunk diameters, while PVAc achieved slightly higher bonding efficiency. Wettability remained stable across zones and surfaces. A bibliometric analysis highlighted increasing global interest in rubberwood and bio-based materials for sustainable construction, emphasizing its relevance to the Sustainable Development Goals (SDGs) and its potential as a renewable material for green innovation.